O8: DIRECT MANIPULATION OF THE INTESTINAL MICROBIOME TO INFLUENCE POST‐OPERATIVE OUTCOMES. (27th April 2021) - Dilke, SM; Durant, LR; Stentz, R; Wilson, A; Tozer, PJ; Vaizey, CJ; Hoyles, L; Carding, S; Knight, SC; Noble, A
Abstract: Introduction: Distal feeding (DF) involves intubation of the distal limb of a loop ileostomy to feed with a prebiotic mix. Studies suggest that distally feeding patients following anterior resection prior to ileostomy closure may be beneficial as a form of bowel pre‐habilitation. These pilot data examine the adaptive immune response to DF. Method: Ten healthy controls with an intact GI tract were compared with 10 patients following rectal cancer resection and chemo/radiotherapy, prior to closure of ileostomy over 8 weeks of DF. We examined B and T cell memory responses from peripheral blood using cell proliferation assays. Cells were cultured with dead antigen to reflect the microbiota in the small and large bowel. Two negative and two positive controls were used to assess minimal and maximum cell proliferation. Result: B cell responses prior to DF were increased in the defunctioned group compared to the normal controls to significance (p=0.0014). After 8 weeks of DF the groups were comparable. T cell responses to bacteria had significant differences in proliferation rate following DF commencement, CD4 week 0 vs 3 p=0.0001, week 3 vs 8 p=0.000034, CD8 week 0 vs 3 p=0.0001, week 3‐8 p=0.00024). In individual patients, CD4 responses were shown to shift from responses to facultative aerobic species, to strict anaerobes. Conclusion: These data suggest that distal feeding fundamentally resets peripheral circulating memory and it may be of use in pre‐habilitating the bowel prior to restoration of continuity. Early clinical data suggests that distal feeding improves post‐operative outcomes. Take‐home message: distal feeding is an easy pre‐operative intervention that has a significant effect on cell proliferation and antigen response, which may contribute to improved post operative outcomes.